Left atrial myxoma causing severe mitral regurgitation - Vaidyanathan, Swaminathan; Rajakumar, Anjith Prakash; Madhan, Vijay; Kurian, V. M. (International Surgery Journal, 2018)
Myxomas are the most common benign tumours of the heart, majority of them arise from left atrium. They can have varied presentations, with asymptomatic patients to be picked up in routine screening at one end of spectrum to dangerous embolic manifestations at the other end of the spectrum. We report a case of left atrial myxoma distorting the mitral valve apparatus causing severe eccentric mitral regurgitation. Patient underwent complete surgical excision of the tumour along with mitral valve repair.